The Influence of Organizational Culture to Employee in The Financial and Asset Management Agency - Yansahrita Yansahrita (Komunitas Dosen Indonesia, 2019)
In supporting the progress and development of an organization, it is very necessary to be carried out seriously and continuously in all fields and all aspects of life. The availability of quality human resources and have a high work ethic is the main capital of an organization to be aligned with other organizations. Without the individuals of each individual to try to progress without the need to be forced, an organization does not mean anything. In the financial and Asset Management Agency Regions Ulu Ogan Ogan, it has not been implemented organizational culture so well that Akunta Sector Employee Morale nAnd reporting is not optimal. The problem faced is how the influence of organizational culture on employee morale in the field of accounting and reporting in the Regional Financial and Asset Management Agency of Ogan Komering Ulu. The purpose of this study was to determine the influence of organizational culture on Morale Employees Sector Akunta n si and Reporting on Financial Management Board and Asset Ogan Ogan Ulu and useful as a reference for further research on organizational culture and Morale Employees Sector Akunta n si Dan Reporting. Hypothesis, positive effect on the organizational culture Employee Morale Affairs Akunta n si and Reporting on Financial Management Board and AssetOgan Komering Ulu. Data collection and management using literature study and field studies using observation, questionnaires, interviews and documentation. From the results of the discussion obtained by the correlation between organizational culture in an effort to improve the Employee Morale in the Field of Accounting and Reporting at the Financial Management Agency and the Ogan Komering Ulu Regional Assets obtained r value of 0.57. After consultation with conservative standards, it is located between 0,400-0,599 which is included in the medium relations. So that it can be said that there is a moderate influence between organizational culture on employee morale in the field of Accounting and Reporting at the Ogan Komering Ulu Regional Financial and Asset Agency.